Talent management of knowledge workers : embracing the non-traditional workforce - Vaiman, Vlad, 1971- (New York : Palgrave MacMillan, 2010)
'Freelancers possess a tremendous amount of knowledge, skill, and ability. Identifying, defining, and implementing talent management strategies aimed at ensuring the effective management of non-traditional knowledge employees in an organization are the key themes of this book'--
Includes bibliographical references and index.
Keywords: Knowledge workers -- Case studies; Personnel management -- Case studies